Students’ Ability in Solving Statistical Problem Using the Context of the COVID-19 Pandemic - Hasanah, Mifta Nur; Putri, Ratu Ilma Indra; Zulkardi (Mathematics Education Journal, 2022)
This study aims to determine mathematical abilities of the students in grade 8 in solving statistical problem using RME and LSLC in online learning during the COVID-19 pandemic. Learning began with the provision of were given interactive videos as an asynchronous pre-learning stage. Furthermore, at the synchronous stage, students were given sharing tasks and jumping tasks then synchronous activities were closed by giving independent assignments. In asynchronous pre-learning, students sent independent assignments via Google Classroom at a predetermined time. Subjects in this study were 31 eight graders junior high school students. This research used a descriptive method, where the data were obtained by using observation, test, and interview. The data were analyzed qualitatively descriptively. The result of this study is students’ abilities in a good category with an average 68,5. Therefore, it is concluded that RME and LSLC are suitable for use during a pandemic as teaching methods for statistics.DOI : https://doi.org/10.22342/jpm.16.2.14162.215-226